Film at Wit's End : Eight Avant-Garde Filmmakers. - Brakhage, Stan (New York : McPherson & Company, 1989)
Broughton, Conner, Deren, Hill, Jacobs, MacLaine, Menken, Peterson
boek
Keywords: Brakhage, Stan